2021
DOI: 10.1038/s43247-021-00170-2
|View full text |Cite
|
Sign up to set email alerts
|

Biosignatures of ancient microbial life are present across the igneous crust of the Fennoscandian shield

Abstract: Earth’s crust contains a substantial proportion of global biomass, hosting microbial life up to several kilometers depth. Yet, knowledge of the evolution and extent of life in this environment remains elusive and patchy. Here we present isotopic, molecular and morphological signatures for deep ancient life in vein mineral specimens from mines distributed across the Precambrian Fennoscandian shield. Stable carbon isotopic signatures of calcite indicate microbial methanogenesis. In addition, sulfur isotope varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…(2008) temperature definition in a 3–D sense reveals little difference in “climatic habitability” between worlds that otherwise appear quite climatically distinct. On Earth life has been found to withstand pressures beyond those of deep sea trenches on Earth (e.g., Sharma et al., 2002; Vanlint et al., 2011), at the bottom of thick ice sheets (e.g., Griffiths et al., 2021) and in extremely deep mines (e.g., Drake et al., 2021; Lollar et al., 2019). Given enough time life has found a way to fill nearly every ecological niche on the modern Earth.…”
Section: Resultsmentioning
confidence: 99%
“…(2008) temperature definition in a 3–D sense reveals little difference in “climatic habitability” between worlds that otherwise appear quite climatically distinct. On Earth life has been found to withstand pressures beyond those of deep sea trenches on Earth (e.g., Sharma et al., 2002; Vanlint et al., 2011), at the bottom of thick ice sheets (e.g., Griffiths et al., 2021) and in extremely deep mines (e.g., Drake et al., 2021; Lollar et al., 2019). Given enough time life has found a way to fill nearly every ecological niche on the modern Earth.…”
Section: Resultsmentioning
confidence: 99%
“…The detected paleome signatures cannot reflect the metabolic potentials of microbes colonizing sediments about 240 million years ago, when the Upper Muschelkalk and Lower Keuper (lithostratigraphic subgroups of the Middle Triassic) were formed [92]. Our paleome signatures cannot be considered as biosignatures from ancient microbial life over geological time periods, as those identified in calcite and pyrite veins across the Precambrian Fennoscandian shield by isotopic and molecular analyses [93]. Rather carbonate bedrocks represent DNA archives that can be used to learn more about the near biological past.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the crystalline bedrock can sometimes host organic carbon (such as bitumen/seep oil) within fracture networks [41,42]. Migration of organic matter from organic-rich source rock into to fractured crystalline basement during burial heating has been suggested in localities such as the Siljan impact structure in Sweden [43] and the Bergslagen area [22,31] of the Fennoscandian shield. The bitumen and seep oil are associated with thermogenic methane but can also provide a ready energy source for microbial activity [30,41].…”
Section: Methane In the Crystalline Crustmentioning
confidence: 99%
“…The importance of viral predation exerting top-down control on microbial communities in the terrestrial deep biosphere, also suggests that the predation of viruses on the microbial communities may provide an important resource of organic carbon to the deep ecosystems [28]. In addition, recent investigations of biosignatures in secondary mineral coatings and fossilized microbial remains in deep crystalline bedrock fractures of the Fennoscandian shield have revealed that microbial methanogenesis and anaerobic oxidation of methane have been widespread processes in the deep subsurface over hundreds of millions of years [22,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%